Muhammad Abduh's Adabî-Ijtima'î pattern in Tafsir al-Manar - Akhmad Jazuli Afandi (IAIN Madura, 2023)
This article aims to examine in depth the style of interpretation of adabî-ijtima’î. Muhammad Abduh considered some books of tafsir at that time and earlier times to be arid and rigid, because many interpreters directed attention to linguistic technicalities without paying attention to social aspects and eventually moved away from the purpose of the Qur'an. Abduh gave a breakthrough to this problem by presenting the style of tafsir adabî-ijtima’î, which is a style of interpretation of the Quran whose presentation emphasizes the beauty of language (literature). At the same time, the description of the discussion is more directed at socio-cultural criticism and community improvement based on the hidayah of the Qur'an. This article is the result of library research using a descriptive-analytical approach. The ijtima'î style is a tafsir that emphasizes an in-depth study of social and socio-cultural conditions by finding social